2018
DOI: 10.1038/s41598-018-32519-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in depth RNA sequencing of P. tricornutum’s morphotypes reveals specific features of the oval morphotype

Abstract: Phaeodactylum tricornutum is the most studied diatom encountered principally in coastal unstable environments. It has been hypothesized that the great adaptability of P. tricornutum is probably due to its pleomorphism. Indeed, P. tricornutum is an atypical diatom since it can display three morphotypes: fusiform, triradiate and oval. Currently, little information is available regarding the physiological significance of this morphogenesis. In this study, we adapted P. tricornutum Pt3 strain to obtain algal cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(85 citation statements)
references
References 76 publications
9
73
0
Order By: Relevance
“…These residues have been demonstrated by directed mutagenesis to be involved in the binding to the acceptor substrate. Based on RNA-seq data recently reported in Ovide et al (2018), mainly Phatr3_J46109 and Phatr3_J54599 are expressed in the three morphotypes of P. tricornutum (fusiform, triradiate, and oval morphotypes).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These residues have been demonstrated by directed mutagenesis to be involved in the binding to the acceptor substrate. Based on RNA-seq data recently reported in Ovide et al (2018), mainly Phatr3_J46109 and Phatr3_J54599 are expressed in the three morphotypes of P. tricornutum (fusiform, triradiate, and oval morphotypes).…”
Section: Resultsmentioning
confidence: 96%
“…The P. tricornutum strain Pt1.8.6 (CCAP1055/1) was grown in reconstituted artificial seawater (AQUARIUM SYSTEMS Instant Ocean) enriched with Conway medium containing 80 mg.L −1 of sodium metasilicate (Na2SiO3), at 19 ± 1°C as described previously in Ovide et al, 2018. The culture were grown under a 16 h/8 h light/night cycle (280–350 μmol photons m −2 ⋅s −1 ) and agitation at 150 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We carried out a series of laboratory experiments in suspensions of the planktonic fusiform morphotype of P . tricornutum (5759). The LISST-100× Small Volume Flow Through Chamber (Sequoia Scientific, Inc.) was precleaned and filled with the desired vol/vol concentration of cell culture in growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we show that the induced expression of GPCR1A is sufficient to shift morphotypes, pointing to this protein as a potential target protein of screening anti-biofouling compounds. A comparative RNA-seq study on Phaeodactylum morphotypes was recently reported on the strain Pt3 ( Ovide et al., 2018 ), in which the major morphotype is oval (60%–75%) under liquid culture conditions. This phenotypic ratio is uncommon and is different in other strains of P .…”
Section: Discussionmentioning
confidence: 99%